Continuity and Change: Performing Gender in Rural Tanzania - Badstue, Lone B.; Farnworth, Cathy Rozel; Umantseva, Anya; Kamanzi, Adelbertus; Roeven, Lara (Informa UK Limited, 2021)
Tanzanian legislation for women’s rights is a product of decades of indigenous women’s struggles and considered amongst the most progressive in Africa. However, implementation has been problematic and some elements in the current discourse appear to push back against gender equality with an essentialist framing of women and men as naturally different. This paper draws on the perspectives of 144 women and 144 men, in four rural communities in different regions of Tanzania, to build an understanding of how they perceive gender equality, and how their perceptions relate to decision-making, women earning incomes, women as homemakers, and control over assets. Understanding gender as a performance we contextualise our analysis through a historical overview of women’s struggles to secure rights from colonial times to the present day. We find that while local discourse appears to embrace the idea of gender equality, practice remains quite different with the threat of sanctions restricting the scope for re-negotiation of gender. The paper demonstrates how the continuous performance, reproduction and renegotiation of gender takes place as part of everyday life, as women and men seek to secure their personal well-being in a context of limited cultural and economic options.